NEW SUBFAMLY, GENUS AND SPECIES OF LOWER CARBONIFEROUS RUGOSE CORALS FROM CENTRAL ALBORZ (N. IRAN) (Journal of Sciences, Islamic Republic of Iran)
Carboniferous strata in the Alborz mountains consist of calcareous rich fossils the main part of which is composed of rugose corals. There have been few studies carried out on corals so far. In this paper, a new subfamily, genus and eight new species of rugose corals from Mobarak limestones in the central Alborz mountains are introduced